YOUTH POLICY IN NEW UZBEKISTAN (Conference Zone, 2022)
Looking back on the multi-century history of the Uzbek people, you can see the difficult stages of conquering the peaks of development. (Matthew 24:14; 28:19, 20) At these stages, there are important processes, such as the formation of our statehood, the rise of science, art, and culture in society, and the achievements of our great ancestors in their work